Review: Validation of Liquid Chromatography Analysis Methods for Anti-cancer Compounds - Hutauruk, Grace Natasya (Universitas Dehasen Bengkulu, 2023)
Cancer is a disease with many variations and a high level of morbidity. Cancer therapy has significant development with the emergence of new anti-cancer compounds and using combinations of anti-cancer compounds. Therefore, a simple and appropriate analytical method is needed for the analysis of anti-cancer compounds in various sample forms. Liquid chromatography is a common method of analysis. This review will provide information on the validation of liquid chromatography analysis methods in the analysis of anticancer compounds. Parameters observed were linearity, accuracy and precision, sensitivity and specificity, and system suitability.